2018
DOI: 10.1155/2018/8429145
|View full text |Cite
|
Sign up to set email alerts
|

Ammonia-Oxidizing Archaea (AOA) Play with Ammonia-Oxidizing Bacteria (AOB) in Nitrogen Removal from Wastewater

Abstract: An increase in the number of publications in recent years indicates that besides ammonia-oxidizing bacteria (AOB), ammonia-oxidizing archaea (AOA) may play an important role in nitrogen removal from wastewater, gaining wide attention in the wastewater engineering field. This paper reviews the current knowledge on AOA and AOB involved in wastewater treatment systems and summarises the environmental factors affecting AOA and AOB. Current findings reveal that AOA have stronger environmental adaptability compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 65 publications
1
42
0
Order By: Relevance
“…AO will generate N 2 O in aerobic processes, but their contributions will be influenced by spatial heterogeneity, with anoxic conditions within flocs of activated sludge processes and biofilms formed in trickling filters. AOB are generally considered to dominate AO communities, but Yin, Bi, and Xu (2018) found that AOB dominated 13 of 23 wastewater treatment plants, including 3 in which AOA were not detectable. AOB are generally considered to dominate AO communities, but Yin, Bi, and Xu (2018) found that AOB dominated 13 of 23 wastewater treatment plants, including 3 in which AOA were not detectable.…”
Section: Wastewater Treatment Systemsmentioning
confidence: 99%
“…AO will generate N 2 O in aerobic processes, but their contributions will be influenced by spatial heterogeneity, with anoxic conditions within flocs of activated sludge processes and biofilms formed in trickling filters. AOB are generally considered to dominate AO communities, but Yin, Bi, and Xu (2018) found that AOB dominated 13 of 23 wastewater treatment plants, including 3 in which AOA were not detectable. AOB are generally considered to dominate AO communities, but Yin, Bi, and Xu (2018) found that AOB dominated 13 of 23 wastewater treatment plants, including 3 in which AOA were not detectable.…”
Section: Wastewater Treatment Systemsmentioning
confidence: 99%
“…Two species of Archaea, Haloferax denitrificans a nd Pyrobaculum aerophilum have been reported to produce N 2 gas as the final end product indicating the complete mechanism of denitrification (De Vries and Schroder ). In recent years, Archaea have been successfully cultivated and enriched, but still, there is not much information on the enrichment of Archaea in actual wastewater nitrogen‐removal systems (Yin et al ). However, the role of bacteria in denitrification has been more extensively studied.…”
Section: Biological Routes Of Nitrate Removalmentioning
confidence: 99%
“…A cell morphology consisting of membrane‐bound compartments may be better at protecting the cell from toxic compounds compared to a typical prokaryote cell, where key enzymes often are accessible in the periplasm. It is well‐established that nitrifying microorganisms (AOB and ammonia oxidizing archaea, AOA) have their key ammonia oxidizing enzyme, AMO, in the periplasm . The periplasmic location of the Cu‐containing AMO may account for the heightened sensitivity of AOB to azoles.…”
Section: Discussionmentioning
confidence: 99%
“…It is well-established that nitrifying microorganisms (AOB and ammonia oxidizing archaea, AOA) have their key ammonia oxidizing enzyme, AMO, in the periplasm. 34 The periplasmic location of the Cu-containing AMO may account for the heightened sensitivity of AOB to azoles. However, the relatively low toxicity of the azole compounds to anammox also may be related to the unique cell membrane structure/composition of the anammox bacteria.…”
Section: Discussionmentioning
confidence: 99%